KEANEKARAGAMAN JENIS DAN POLA SEBARAN TUMBUHAN OBAT DI HUTAN RAWA GAMBUT RESORT SEBANGAU HULU TAMAN NASIONAL SEBANGAU KALIMANTAN TENGAH - Nisfiatul Hidayat; Hendra Toni; Salmansyah Salmansyah (Agrienvi: Jurnal Ilmu Pertanian, 2023)
This study aims to determine the species diversity and distribution pattern of medicinal plants in the peat swamp forest at ​​Sebangau Hulu Resort, Sebangau National Park, Central Kalimantan. Based on the results of the study, there were 19 types of medicinal plants in the peat swamp forest at the Sebangau Hulu Resort, which include to 15 families. Medicinal plants at the seedling and sapling level were dominated by Tatumbu (Syzygium sp.), and Jinjit (Calophyllum soulatri), while at the pole and tree level it was dominated by Piais (Nephelium lapaceun L.), Beside these types,  Latak Manuk (Ctenolophon parvifolius Oliver) was a species that also dominant at the stake and pile level. Species diversity of medicinal plant  includes low to moderate classification, species richness includes low classification, and evenness includes high classification. The distribution pattern of medicinal plants at the seedling and sapling level has an aggregated pattern, while at the pole and tree level it has a random pattern.